Evaluasi Aktivitas Penghambatan α-Amilase, α-Glukosidase, dan Aktivitas Antioksidan secara In Vitro dari Ekstrak Etanol Lima Sayuran Indonesia: Pendekatan Multivariat dan Korelasi - Nofrizal Nofrizal; Fatma Haspa Anzalmi; Lusia Eka Putri (Journal of Pharmaceutical and Sciences, 2026)
Postprandial hyperglycemia and its associated oxidative stress are recognized as pivotal pathological hallmarks driving the progression of type 2 diabetes mellitus and its vascular complications. This study aims to evaluate and comparatively analyze the in vitro α-amylase, α-glucosidase inhibitory activities, alongside the free radical scavenging capacities, of ethanolic extracts derived from five widely consumed fresh vegetables in Indonesia: Carica papaya, Momordica charantia, Gigantochloa atter, Diplazium esculentum, and Luffa acutangula. Bioactivity assays were conducted utilizing starch-iodine, p-nitrophenyl-α-D-glucopyranoside, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) methodologies. The experimental findings demonstrated that D. esculentum extract exhibited the most pronounced dual-inhibitory efficacy against α-amylase (IC50 138.50 µg/mL) and α-glucosidase (IC50 38.20 µg/mL). Furthermore, D. esculentum and C. papaya extracts demonstrated strong antioxidant capacities among all evaluated samples. Principal Component Analysis (PCA) and Pearson correlation analyses confirmed a strong positive correlation between free radical scavenging capacity and carbohydrate-hydrolyzing enzyme inhibition. In conclusion, D. esculentum emerges as a premier functional vegetable candidate, exhibiting remarkable dual-action therapeutic properties for the attenuation of postprandial hyperglycemia and mitigation of oxidative stress.